Memorandum on Programme and Research for Development of Natural Resources - Planning Commission (Planning Commission, 1956)
The Panel of Scientists was constituted in April, 1956, to advise and assist the Planning Commission in linking up programmes of scientific study and investigations in the national laboratories, in universities and in many institutions which are maintained and supported by Government, as closely as possible, with the requirements of national planning.
Planning Commission
Planning Commission